TEKNOLOGI AKUAPONIK DENGAN TANAMAN YANG BERBEDA TERHADAP PERFORMA PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Prama Hartami; Nazarul Syahputra; Erlangga Erlangga (Universitas Teuku Umar, 2015)
This study was conducted on July 28th to August 02nd 2014 in Laboratory of Hatchery and Aquaculture Technology which aimed to determine the effectiveness of aquaponictechnology to incorporate different types of plants to growth performance of tilapia. The benefit of this research was as useful information to aquaculture field, especially to maximalized fish growth technology. The method used in this study was non factorial completely randomized design with 4 treatments and three replications. The results showed the value of water quality such as mmonia 0.02 mg/l, turbidity 4.67 NTU, lenght growth 3.65 cm and a weight of 9.68 grams with a value of survival rate 96.66%, feed conversion 1.08% and long growth of plants 22.10 cm where Fcount> Ftable.